The externalizing spectrum in youth: Incorporating personality pathology. Issue 5 (18th November 2013) - Tackett, Jennifer L.; Herzhoff, Kathrin; Reardon, Kathleen W.; De Clercq, Barbara; Sharp, Carla
ABSTRACT: Although personality disorder characteristics are often grouped with externalizing problems in adults, little is known about the extent to which they define the externalizing spectrum in youth. We examined the extent to which personality pathology traits in youth reflected common and specific variance in externalizing problems and explored differentiation of these connections by age. Parents reported on physical aggression, rule‐breaking, relational aggression, and personality pathology traits for 1080 youth (48.8% male) ages 6–18 years. Disagreeableness and emotional instability traits were correlated with a general externalizing factor as well as with specific behavioral subfactors. The magnitude of these correlations varied across age, with the highest magnitude evidenced during the developmental periods of greatest prevalence for the specific externalizing behavior subtype. Taken together, these findings suggest that personality pathology is tightly connected with externalizing problems in youth, especially during developmental periods when externalizing problems are common.